Clinical values of 18F‐FDG PET/CT in oral cavity cancer with dental artifacts on CT or MRI. Issue 6 (3rd July 2014) - Hong, Hye Ran; Jin, Soyoung; Koo, Hyun Jung; Roh, Jong‐Lyel; Kim, Jae Seung; Cho, Kyung‐Ja; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
<x xml:space="preserve">Abstract</x> Level of Evidence: 2a Background and Objectives: To investigate the role of 18F‐FDG PET/CT in tumor staging, extent, and volume measurements in oral cavity squamous cell carcinoma (OSCC) patients with/without dental artifacts on CT or MRI. Methods: This study was conducted in 63 consecutive patients with OSCC who received initial workups including 18F‐FDG PET/CT and MRI. The results of the imaging modalities were compared to those of pathology, using McNemar's test and the paired t‐test. Results: Thirty‐seven patients (59%) had dental or metallic artifacts obscuring primary tumors. 18F‐FDG PET/CT scanning was superior to MRI in tumor staging (weighted κ = 0.870 vs. 0.518, P = 0.004) in patients with dental artifacts. In addition, 18F‐FDG PET/CT scans were more specific than MRI in detecting sublingual gland (P = 0.014) and mouth floor (P = 0.011) involvement. In patients with dental artifacts, there was a significant discrepancy between primary tumor volume (PTV) measured by pathology and MRI (P = 0.018), but not between PTV measured from pathology and 18F‐FDG PET/CT at SUV2.5 (P = 0.245), which showed the highest intraclass correlation coefficient value (0.860). Conclusion: 18F‐FDG PET/CT scans provide accurate tumor staging and volume measurements in OSCC patients with CR/MRI dental artifacts, leading to improved preoperative planning. Level of Evidence: 2b CONDENSED ABSTRACT This study evaluated the clinical value of 18F‐FDG PET/CT in 63 patients with oral cavity cancers. In 37 (59%) patients with dental artifacts on CT/MRI, 18F‐FDG PET/CT showed superior results compared to MRI in tumor staging and represented the highest intraclass correlation coefficient value to tumor volume determined by pathology. J. Surg. Oncol. 2014 110:696–701. © 2014 Wiley Periodicals, Inc.